(untitled) (Central Asian Journal of Medical Sciences, 2023)
Objectives: Kimura’s disease (KD), or eosinophilic lymphogranuloma, is a rare chronic inflammatory condition with unclear etiology. We aim to present our experience with this condition and review the available literature. Methods: This report depicts a pathologically proven case of KD in a 44-year-old man with gradually increased swelling in his left parotid region for the past year, which was painless, and pruritus. Results: This report depicts a pathologically proven case of KD in a 44-year-old man with gradually increased swelling in his left parotid region for the past year, which was painless, and pruritus. Conclusion: This report depicts a pathologically proven case of KD in a 44-year-old man with gradually increased swelling in his left parotid region for the past year, which was painless, and pruritus.